Bahasa dan sastra Inggris (peminatan) : untuk SMA/MA Kelas XII Semester 2 (2018)
Buku ini berisi 4 bab yang mewakili setiap kompetensi dasar untuk mata pelajaran Bahasa dan Sastra Inggris kelas XII Kelompok Peminatan, Bab I, Bringing Mobile Phone to School : concept chart, apperception, discussion text, exercise, activity, competence test, remedial, enrichment, glossary,.......Bab 2, Although she has stroke, she still has....., : concept chart, apperception, concessive clause, exercise, activity, competence test, remedial, enrichment, glossary Bab 3 The movie is very inspirational, ...: concept chart, apperception, concessive clause, exercise, activity, competence test, remedial, enrichment, glossary Bab 4, Song. : concept chart, apperception, how to analyze a song, exercise, figurative language in song, exercise, concept chart, apperception, concessive clause, exercise, activity, competence test, remedial, enrichment, glossary